2018
DOI: 10.1158/0008-5472.can-17-2906
|View full text |Cite
|
Sign up to set email alerts
|

Transketolase Regulates the Metabolic Switch to Control Breast Cancer Cell Metastasis via the α-Ketoglutarate Signaling Pathway

Abstract: Although metabolic reprogramming is recognized as a hallmark of tumorigenesis and progression, little is known about metabolic enzymes and oncometabolites that regulate breast cancer metastasis, and very few metabolic molecules have been identified as potential therapeutic targets. In this study, the transketolase (TKT) expression correlated with tumor size in the 4T1/BALB/c syngeneic model. In addition, TKT expression was higher in lymph node metastases compared with primary tumor or normal tissues of patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 37 publications
5
67
0
Order By: Relevance
“…Besides the upregulated genes in the glycolysis pathway, G6PD and TKT in the pentose phosphate pathway were also consistently upregulated, which predicted worse survival. This is consistent with previous reported functions of these two genes associated with aggressiveness of the disease and drug resistance in other cancer types [54][55][56][57][58]. Most of the genes involved in glycogen metabolism such as GYS2, UGP2, and AGL had down-regulated expression when compared to normal tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Besides the upregulated genes in the glycolysis pathway, G6PD and TKT in the pentose phosphate pathway were also consistently upregulated, which predicted worse survival. This is consistent with previous reported functions of these two genes associated with aggressiveness of the disease and drug resistance in other cancer types [54][55][56][57][58]. Most of the genes involved in glycogen metabolism such as GYS2, UGP2, and AGL had down-regulated expression when compared to normal tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the reduction of TKT is responsible for a switch from glycolysis to OXPHOS. Consistent with these results, combinations of the TKT inhibitor oxythiamine, docetaxel, and doxorubicin enhance cell death in triple-negative breast cancer cells [57]. In line with these studies, and consistent with what was anticipated in a previous section in this review, we contributed to shedding further light on the correlation between drug resistance and cancer metabolic remodeling through the characterization in several cancer types of the molecular chaperone TRAP1, which has been extensively described for its role in the stress adaptive response of cancer cells, and has recently emerged as a critical regulator of cancer cell metabolism and chemoresistance.…”
Section: Metabolic Enzymes and Cancersupporting
confidence: 68%
“…Catalyzes the phosphorylation of glucose to generate glucose-6-phosphate in the first step of glycolysis. It promotes chemoresistance by enhancing cisplatin-induced autophagy OC [117,118] Transketolase (TKT) Ezyme catalyzing important reaction both in the Calvin cycle and in pentose phosphate pathway BC [57]…”
Section: Function Tumor Type Referencesmentioning
confidence: 99%
“…In addition, G6PD expression and activity are continuously unregulated in breast cancer cells, and it has been reported that G6PD inhibition leads to an increase in 5'-AMP-activated protein kinase (AMPK) signaling, a decrease in lipid biosynthesis and the inhibition of breast cancer cell growth and survival (21). Furthermore, TKT expression is associated with tumor size in the 4T1/BALB/c syngeneic model, and high TKT levels are associated with poor survival (87).…”
Section: Ppp In Malignant Tumorsmentioning
confidence: 99%